ANALISIS UNSUR KEBUDAYAAN DALAM NOVEL “ISLAMMU ADALAH MAHARKU” KARYA ARIO MUHAMMAD DENGAN PENDEKATAN MIMETIK - Moh. Hadi Purnomo; Maya Tri Hamidah; Hania Shinta Rahma Putri (Kajian Linguistik dan Sastra, 2021)
This research is a research on the analysis of prose literature in the novel "Islammu Is Maharku" by Ario Muhammad. This study specializes in literary studies based on a mimetic approach. The mimetic approach is an approach that examines literary works based on their relationship to reality or reality in life. The author chooses cultural elements based on the mimetic approach in this study. The research method used descriptive qualitative and then the data were analyzed by interactive analysis. The purpose of this study is to describe the cultural elements in the novel "Islammu is Maharku" by Ario Muhammad with a mimetic approach. The results of the discussion describe the cultural reality of Taiwan based on: (1) The religious system, some believe in God and some are anti-God; (2) The social system and social organization, the existence of a society that has a high work spirit, many women who are reluctant to marry, and Muslim life in Taiwan; (3) Knowledge systems, knowledge of the world for example the seasons; (4) Language, Indonesian, English, Mandarin, but some have been changed into Indonesian by the author; (5) the arts, the beauty of the landscape and the buildings of the city of Taiwan; (6) Livelihood system or economic system, mostly as students and lecturers; and (7) Live equipment systems or highly advanced technology.Keywords: novel, culture, taiwan, mimetics